Abelian vectors and self-dual tensors in six-dimensional supergravity - Chandía, Osvaldo [UNESP] (Elsevier, 2000)
In this note we describe the most general coupling of abelian vector and tensor multiplets to six-dimensional (1,0) supergravity. As was recently pointed out, it is of interest to consider more general Chern-Simons couplings to abelian vectors of the type H(r) = dB(r) - 1/2 c(rab)AadAb, with c(r) matrices that may not be simultaneously diagonalized. We show that these couplings can be related to Green-Schwarz terms of the form B(r)c(r)/abFaFb, and how the complete local Lagrangian, that embodies factorized gauge and supersymmetry anomalies (to be disposed of by fermion loops) is uniquely determined by Wess-Zumino consistency conditions, aside from an arbitrary quartic coupling for the gauginos. (C) 2000 Elsevier Science B.V.
Keywords: energy; gravity; mathematical analysis; theory